Fostering an Attitude of Nationalism to the Students of SMP Negeri Panjatan Through The Philosophical Value of Batik Gebleg Renteng Toward The Values of Pancasila - Andi Andoko; Warto Warto; Djono Djono (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
This study aims to foster the nationalistic attitude of students of SMP Negeri Panjatan, Kulon Progo Regency, Yogyakarta Special Region through the philosophical values of Gebleg Renteng related to Pancasila values. This research uses descriptive qualitative method. The data sources are taken from books, journals and supporting documents related to research. The main characteristics in the research come from the natural / reality background at Panjatan State Junior High School by observing, interviewing, and analyzing documents. After the data is collected, the researcher analyzes and then concludes the results of the data that have been obtained. The results of this study are the motifs in the Gebleg Renteng batik, including Gebleg in the form of a figure eight combined into one bond (jointly), the kacer bird, the mangosteen fruit, the binangun symbol, the Kulon Progo logo, up and down patterns and other variations. Gebleg Renteng's batik motif can be taken from a philosophical value, namely nationalism. Values are always associated with moral ethics or character so that the philosophical values in Gebleg Renteng's batik can be used to foster students' nationalistic attitudes through learning. An attitude of nationalism must be instilled in the younger generation in order to understand the importance of the Indonesian struggle for independence. The value contained in Gebleg Renteng's batik is nationalism in accordance with what is the basis of the Republic of Indonesia, namely Pancasila. Pancasila is an Indonesian state ideology which has very meaningful values in building the nation and state. Pancasila is taken from the values of customs, cultural and religious values that exist in the life of the Indonesian people so that Pancasila must be maintained for the integrity of the Unitary State of the Republic of Indonesia.